An Analysis Contextual Meaning on “Snow White and The Seven Dwarfs” Movie - Etika Dewi Kusumaningtyas; Ayuk Dian Khafita (Universitas An Nuur, 2022)
This research in title “An Analysis Contextual Meaning On “Snow White And The Seven Dwarfs”. The problems of this research are: is there any contextual meaning on Snow White and The Seven Dwarfs. The researcher used descriptive qualitative method. The purpose of this research is to know contextual meaning on Snow White and The Seven Dwarfs. In collecting data, the writer concentrates the utterances which contains words which has more than one meaning. The result of the research, there are 20 words with more than one meaning.